Achieving carbon-neutral iron and steelmaking in Europe through the deployment of bioenergy with carbon capture and storage. (1st May 2019) - Mandova, Hana; Patrizio, Piera; Leduc, Sylvain; Kjärstad, Jan; Wang, Chuan; Wetterlund, Elisabeth; Kraxner, Florian; Gale, William
Abstract: The 30 integrated steel plants operating in the European Union (EU) are among the largest single-point CO2 emitters in the region. The deployment of bioenergy with carbon capture and storage (bio-CCS) could significantly reduce their emission intensities. In detail, the results demonstrate that CO2 emission reduction targets of up to 20% can be met entirely by biomass deployment. A slow CCS technology introduction on top of biomass deployment is expected, as the requirement for emission reduction increases further. Bio-CCS could then be a key technology, particularly in terms of meeting targets above 50%, with CO2 avoidance costs ranging between €60 and €100 tCO2 −1 at full-scale deployment. The future of bio-CCS and its utilisation on a larger scale would therefore only be viable if such CO2 avoidance cost were to become economically appealing. Small and medium plants in particular, would economically benefit from sharing CO2 pipeline networks. CO2 transport, however, makes a relatively small contribution to the total CO2 avoidance cost. In the future, the role of bio-CCS in the European iron and steelmaking industry will also be influenced by non-economic conditions, such as regulations, public acceptance, realistic CO2 storage capacity, and the progress of other mitigation technologies. Highlights: Bio-CCS can help iron and steel making become close to carbon neutral. Average bio-CCS avoidance cost in the EU is about €80 tCO2 −1 . Netherlands, France, and Belgium have the lowest bio-CCS deployment cost.